Interconnecting Issueof Government’s Regional Budget Allocation and Open Burning Behavior: Study from Indonesia - Mayang Wulandari Naro Putri (The Journal of Indonesia Sustainable Development Planning, 2020)
This research aims to analyze whether people’s perception, living area such as rural/urban, and regional budget proportion for the environment at province level influence open burning behavior of a household in Indonesia. Using household-leveldata in 2017from the National Socioeconomic Survey of Indonesia and adding control factors such as socio-demographic characteristics, a logit regression method is conducted. The result reveals that burning behaviorperception has an important role in open burning thrash decisions and people living in rural areas tend to do open burning trash compared to those who are living in urban areas. Furthermore, provinces with higher proportion budgets for environmental facilities tend to have fewer open burning cases done by households compared to provinces with lower proportion budgets for environment. The findings suggest that government should improve waste policies atregional and municipallevelto reduce open burning trash behavior of households.